Desigualdad e inclusión: La ruta del estado de seguridad social chileno, 1920–1970. - Rengifo, Francisca (Hispanic American Historical Review, 2017)
This article analyzes the institutionalization of Chilean social security policy and its unequal distribution of resources from 1920 to 1970. From 1924 to 1931, when new labor legislation was introduced, Chile built a social security system divided into two major bodies: one comprehensive and public, the other private and organized by type of employment. This article seeks to demonstrate that the combined efforts of these two sectors to extend benefits to the entire Chilean population were insufficient to eradicate inherent inequalities. To explain this trajectory, the article examines the legally defined space for action by public, semipublic, and private administrative entities in which the various actors discussed and negotiated how to implement social security. This implementation was not an inevitable outcome but rather the result of a series of specific policy choices. This perspective allows insight into how the paradigm of welfare as a social right resulted in practice in segmented social security policy.